Integrated Physiological, Transcriptomic, and Proteomic Analyses Reveal the Regulatory Role of Melatonin in Tomato Plants' Response to Low Night Temperature - Xiaolong Yang; Yumeng Zhang; Ting Liu; Jiali Shi; Mingfang Qi; Yufeng Liu; Tianlai Li (MDPI AG, 2022)
Melatonin is a direct free radical scavenger that has been demonstrated to increase plants' resistance to a variety of stressors. Here, we sought to examine the effect of melatonin on tomato seedlings subjected to low night temperatures using an integrated physiological, transcriptomic, and proteomic approach. We found that a pretreatment with 100 μM melatonin increased photosynthetic and transpiration rates, stomatal apertures, and peroxidase activity, and reduced chloroplast damage of the tomato plant under a low night temperature. The melatonin pretreatment reduced the photoinhibition of photosystem I by regulating the balance of both donor- and acceptor-side restriction of PSI and by increasing electron transport. Furthermore, the melatonin pretreatment improved the photosynthetic performance of proton gradient regulation 5 (SlPGR5) and SlPGR5-like photosynthetic phenotype 1 (SlPGRL1)-suppressed transformants under a low night temperature stress. Transcriptomic and proteomic analyses found that the melatonin pretreatment resulted in the upregulation of genes and proteins related to transcription factors, signal transduction, environmental adaptation, and chloroplast integrity maintenance in low night temperature-stressed tomato plants. Collectively, our results suggest that melatonin can effectively improve the photosynthetic efficiency of tomato plants under a low night temperature and provide novel insights into the molecular mechanism of melatonin-mediated abiotic stress resistance.